1967
DOI: 10.1071/ch9670171
|View full text |Cite
|
Sign up to set email alerts
|

Two crystal forms of titanium(IV) methoxide

Abstract: The structure of metal alkoxides has received considerable attention in recent years1-' but polymorphism in this class of compounds has not been reported.Titanium(1v) methoxide was first prepared by Bischoff and Adkins8 by an ester interchange reaction. The product (compound A) is a white insoluble powder. Dunno prepared the methoxide from titanium tetrachloride and methanol in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…In far-IR spectra (Fig. 2), compounds 4 and 5 show strong absorptions in the range of 425e500 cm À1 , which are consistent with the reported n TieCl and n TieO absorptions [28,29]. In comparison with 4, compound 5 shows one more peak that could be due to the vibration of TieO bond in 5.…”
Section: Titanium Complexessupporting
confidence: 89%
“…In far-IR spectra (Fig. 2), compounds 4 and 5 show strong absorptions in the range of 425e500 cm À1 , which are consistent with the reported n TieCl and n TieO absorptions [28,29]. In comparison with 4, compound 5 shows one more peak that could be due to the vibration of TieO bond in 5.…”
Section: Titanium Complexessupporting
confidence: 89%
“…One isomer (I), belonging to the C i point group, is built from three interconnected titanium oxide tetrahedra with a linear arrangement of titanium atoms. This structure have a titanium oxide skeleton similar to that of Ti 3 (OH) 12 . The other isomer (II), of C 2 symmetry, is built by edge sharing TiO 6 groups.…”
Section: Introductionmentioning
confidence: 93%
“…The X-ray diffraction study of single crystal grown from this solution has revealed the tetrameric structure of the B modification [6]. Spectroscopic studies [12,13] also evidence the presence of tetramers in the B phase. However, the structure of the A modification remains uncertain.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations